Rencana Implementasi Penelitian Hadis pada PTKI di Indonesia: Sebuah Analisis Kebijakan - Wahyudin Darmalaksana; Busro Busro (Syaikhuna: Jurnal Pendidikan dan Pranata Islam, 2020)
This study aims to discuss the implementation plan of hadith research based on the National Religious Research Agenda at Islamic Religious Higher Education in Indonesia. This research method is qualitative through literature study with policy analysis. The discussion of this research includes strategic issues of Islamic religious research, priority agenda for Islamic religious research, and plans for implementing hadith research in Islamic Higher Education. The conclusion of this study is that the implementation of hadith research is a sustainable agenda in implementing compliance with policies towards competitiveness in a distributed global arena for academics at undergraduate, master and doctoral levels in the Islamic Religious Higher Education in Indonesia.